SO2 = S + O2
H2SO3 = SO2+H2O
KCl = 2K + Cl2
2FE(OH)3 = Fe2O3 + 3H2O
Mg(OH)2 = MgO + H2O
MgBr2 + BaSO4 = MgSO4 + BaBr2
Объяснение:
H2SO4 + Na2CO3 = Na2SO4 + CO2↑ + H2O
2H(+) + SO4(2-) + 2Na(+) + CO3(2-) = 2Na(+) + SO4(2-) + CO2↑ + H2O
2H(+) + CO3(2-) = CO2↑ + H2O
H2SO4 + 2KOH = K2SO4 + 2H2O
2H(+) + SO4(2-) + 2K(+) + 2OH(-) = 2K(+) + SO4(2-) + 2H2O
H(+) + OH(-) = H2O
H2SO4 + MgO = MgSO4 + H2O
2H(+) + SO4(2-) + MgO = Mg(2+) + SO4(2-) + H2O
2H(+) + MgO = Mg(2+) + H2O
H2SO4 + Fe = FeSO4 + H2
2H(+) +2e = H2(0) 1 в-ие
ок-ль
Fe(0) -2e = Fe(+2) 1 ок-ие
в-ль
H2SO4 + Zn(OH)2 = ZnSO4 + 2H2O
2H(+) + SO4(2-) + Zn(OH)2 = Zn(2+) + SO4(2-) + 2H2O
2H(+) + Zn(OH)2 = Zn(2+) + 2H2O
S + O2 = SO2
SO2 + H2O = H2SO3
K2SO4 + BaCl2 = 2KCl + BaSO4
FeCl3 + 3NaOH = 3NaCl + Fe(OH)3
Mg(NO3)2 + NaOH = NaNO3 + Mg(OH)2
MgSO4 + BaBr2 = BaSO4 + MgBr2